Pictorial essay: Susceptibility-weighted imaging in cerebral ischemia - Mittal Puneet; Kalia Vishal; Dua Sarika (Indian Journal of Radiology and Imaging, 2010)
The susceptiblity effect in magnetic resonance imaging (MRI) has been recognized for long and often has been considered undesirable, producing unnecessary noise. Susceptibility-weighted imaging (SWI) aims at exploiting this effect to provide a different type of contrast that is suited for vascular imaging. We describe five different cases in which SWI was found useful to delineate the underlying ischemia or to arrive at the corect diagnosis.